2003
DOI: 10.1074/jbc.m303591200
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking Phosphatidylinositol Transfer Protein-α Exhibit Spinocerebellar Degeneration, Intestinal and Hepatic Steatosis, and Hypoglycemia

Abstract: Phosphatidylinositol transfer proteins (PITPs) regulate the interface between lipid metabolism and cellular functions. We now report that ablation of PITP␣ function leads to aponecrotic spinocerebellar disease, hypoglycemia, and intestinal and hepatic steatosis in mice. The data indicate that hypoglycemia is in part associated with reduced proglucagon gene expression and glycogenolysis that result from pancreatic islet cell defects. The intestinal and hepatic steatosis results from the intracellular accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(145 citation statements)
references
References 40 publications
9
136
0
Order By: Relevance
“…In yeast, membrane flux through the exocytic pathway is regulated by cytosolic Sec14 [28], a family of cytosolic phosphatidylcholine/phosphatidylinositol transfer proteins that via their dual specificity may act as sensors of lipid composition and adapt lipid metabolism. Whereas one mammalian phosphatidylinositol transfer protein, PITPa, may have a related function and reports back to the nucleus [29], the highly homologous Golgi-associated PITPb is essential for growth [30]. PITPb binds sphingomyelin, which is unexpected as this lipid is thought to be confined to the Golgi lumen.…”
Section: Lipid-binding Proteins and Vesicle Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…In yeast, membrane flux through the exocytic pathway is regulated by cytosolic Sec14 [28], a family of cytosolic phosphatidylcholine/phosphatidylinositol transfer proteins that via their dual specificity may act as sensors of lipid composition and adapt lipid metabolism. Whereas one mammalian phosphatidylinositol transfer protein, PITPa, may have a related function and reports back to the nucleus [29], the highly homologous Golgi-associated PITPb is essential for growth [30]. PITPb binds sphingomyelin, which is unexpected as this lipid is thought to be confined to the Golgi lumen.…”
Section: Lipid-binding Proteins and Vesicle Fluxmentioning
confidence: 99%
“…Based on the prediction that the active center would be similar to that of the lipid phosphate phosphatase (LPP) family, the authors employ a functional cloning strategy in yeast to identify two mammalian sphingomyelin synthases, SMS1 in the Golgi and SMS2 at the plasma membrane, where it is presumably active in ceramide/diacylglycerol-mediated signaling events. [28][29][30]. This paper unravels the mechanism by which the ceramide transfer protein CERT specifically transports ceramide from the ER to the site of Golgi sphingomyelin synthesis [16 ].…”
Section: Updatementioning
confidence: 99%
“…It seems that the decrease of PI-TP protein level may be one of the important factors that lead to disturbing of phospholipids signaling and also may be involved in neurodegeneration of CNS. Alb et al (2002Alb et al ( , 2003 indicated that lack of PI-TPα caused aponecrotic spinocerebrallar disease in PI-TPα knockout mice. The mice lacking PI-TPα die soon after birth (Alb et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In line with being highly conserved in evolution both isomers are essential in cell function. So it was shown that murine embryonic stem (ES) cells deficient in PI-TPa developed normally during embryogenesis, yet the pups died early after birth stemming from complicated organ failure (Alb et al, 2003). On the other hand, PI-TPb gene ablation failed to give viable ES cells (Alb et al, 2002).…”
Section: Introductionmentioning
confidence: 99%